Effect of Corporate Taxation on the Profitability of Firms in NIGERIA - Olaoye Clement Olatunji; Alade Elizabeth Oluwatoyin (Journal of Economics and Behavioral Studies, 2019)
The paper examined the effect of corporate taxation on the profitability of some selected firms in Nigeria from 2007 to 2016 using secondary data which was sourced from various publications of the firms’ financial report. The study employed pooled ordinary least square as the estimation technique. The analytical results revealed that the coefficient of corporate tax on profit after tax was positive with the value of 2.418830 and its P-values were 0.0000, the coefficient of value-added tax was 14.51298 and its p-value was 0.0000. Equally, the coefficient of withholding tax was positive with the value of 7.256489 with p-value 0.0000. Furthermore, education tax result depicts that the coefficient is 36.28245 and it p-value is 0.0000. However, the study concluded that corporate tax rate and education tax as the major taxes paid by companies have positive and significant effects to influence profit after tax. It is also clinched that value-added tax rate and withholding tax being used as other variables that could have effects on profit after tax equally revealed positive and significant effects on profit after tax. Therefore, the study recommended that the government and relevant tax authorities should improve in the administration of corporate taxes to avoid non-compliance